Performance Analysis At The Manpower, Cooperatives And SMEs Department Of Jambi City In 2017-2018 - Sam, Iskandar; Rahayu, Rahayu; Anaguswa, Riri Cofantry (Faculty of Economics and Business Universitas Jambi, 2023)
This study aims to analyze the economy of the Department of Manpower, Cooperatives, and SMEs of Jambi City by examining the percentage comparison of actual spending versus budgeted expenditure. The analysis method used is descriptive, to explain the variables under study. The subjects of this research are respondents from the Department of Manpower, Cooperatives, and SMEs, while the object of the research focuses on the economic analysis for the years 2016-2017. The data used in this study is quantitative, which can be measured or directly counted as numerical variables. Data was collected through an official data collection request sent to the Department of Manpower, Cooperatives, and SMEs of Jambi City. The results show that the performance of the Department in 2017 was 94.7%, and in 2018 it was 93.4%, with an average performance of 94.12% over the 2017-2018 period. Although there was a fluctuation in economic performance, the Department remained highly efficient. The Department was able to reduce its actual spending from 2017 to 2018, ensuring it did not exceed the budget. Despite this reduction, the Department successfully improved skilled labor absorption and the number of quality cooperatives and SMEs in Jambi City.